Building Leadership Capacity Among Student Teachers: A Narrative Inquiry Into Relational Continuity in Student Teachers’ Field Placements (LEARNing Landscapes, 2008)
The authors of this paper are two teacher researchers, one situated at the university and one situated as principal of an elementary school. Through narrative inquiry (Clandinin and Connelly, 2000) two main themes of belonging and becoming were illuminated. The work suggests trusting relationships evolving from dialogue sustained over two field placements at the same school offer student teachers the possibilities of connecting their life experiences with their new experiences at the school; a connected knowing that enables them to develop their identifies as beginning teachers.
Keywords: teacher researcher; elementary school; belonging; becoming; trusting relationship; student teacher; leadership